Strengthening the Capacity of Water-Using Farmers Associations in Desa Kota Datar - Rangkuti, Mohammad Ridwan; Rangkuti, Zoraya Alfathin (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Water as a natural resource that is vital for human life, is increasingly scarce and its availability for agriculture is increasingly limited. For businesses in the agricultural sector, the availability of irrigation water and dams is one of the factors that determine the level of rice field productivity, but the use of water in Kota Datar Village is uneven and inefficient, reflected in the low intensity of food crops (rice and secondary crops). The regulation of irrigation water for lowland rice plants tends to be conventional, wasteful and does not consider cropping patterns in a year. As a result, when there is a long dry season, the stock of water in reservoirs or dams is not sufficient to irrigate rice crops. When the rainy season arrives the water is very abundant, even causing floods, the water is not evenly distributed throughout the irrigation network, so the next planting season will be delayed. Research on strengthening the capacity of the Water User Farmers Association (P3A) is able to answer questions related to reality, especially in Kota Datar Village, which shows that water sources and irrigation networks and dams are not properly maintained and managed. The research objectives are (1) to analyze the characteristics of Gapoktan members/communities, institutional support, and capacity building of WUA members; (2) to analyze capacity strengthening in water management for paddy fields, and its relation to the characteristics of Gapoktan factors, institutional support and capacity building of WUA members; (3) to analyze the level of empowerment in irrigation water management and its correlation with capacity building and institutional strengthening of the P3A Gapoktan; and (4) to formulate a strategy for strengthening capacity in water use towards WUA empowerment in water management for rice fields.